ANTIMICROBIAL ACTIVITY TEST OF 96% ETHANOL EXTRACT OF FLOWERS, LEAVES, AND STEM BARK OF TIGARUN (Crateva magna DC.) AGAINST Staphylococcus aureus and Malassezia furfur - Najwi Hasani; Rika Hartati; Elin Julianti (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Staphylococcus aureus and Malassezia furfur One of the microbes that can cause folliculitis is the inflammation of the skin in the hair follicles. The use of natural ingredients as antimicrobials must be developed as an alternative to overcome the resistance and side effects of chemical drugs. Tigarun (Crataeva magna DC.) is a typical plant in South Kalimantan that can be developed as a natural antimicrobial agent for the treatment of skin infections. Previous studies have reported that tigarun has antimicrobial activity, but no studies have reported its potential antimicrobial activity against folliculitis-causing microbes. Therefore, this study aimed to determine the antimicrobial activity of 96% ethanol extracts of the flowers, leaves, and stem bark of tigarun (Crataeva magna DC.) against microbes that cause folliculitis, including Staphylococcus aureus and Malassezia furfur. Extraction was performed by the maceration method using 96% ethanol. The antimicrobial activities of the extracts were tested using the agar diffusion method. Based on the results of the antimicrobial activity test using the agar diffusion method, the tigarun flower extract showed better antimicrobial activity than the leaf and tigarun bark extracts. Flower extract activity at 200 mg/mL concentrations against Staphylococcus aureus (10.65 ± 0.25) and the fungus Malassezia furfur (7.40 ± 0.40) with moderate inhibition zone ketogenic Keywords: Folliculitis, tigarun, antimicrobial, agar diffusion